Liquefied Synthetic Natural Gas from Woody Biomass - Investigation of Cryogenic Technique for Gas Upgrading - BIRGEN, CANSU; GARCIA, SILVIA (My University, 2013)
Biomass-based liquefied natural gas (bio-LNG) is very valuable renewable fuel as it has high energy density and transportability. Bio-LNG requires liquefaction of the synthetic natural gas (bio-SNG). Cryogenic technology is a promising option for integration of the gas upgrading and liquefaction streams with the main biomass gasification and methane synthesis plant. This thesis investigates the feasibility of this technology for future commercial bio-SNG production plants based on indirect gasification technology, similar to that adopted by Göteborg Energi for the GoBiGas project. Two process configurations for production of bio-LNG from woody biomass are investigated: (1) an integrated configuration which uses cryogenic technology for gas upgrading and liquefaction integrated with the gasification and SNG synthesis plant; (2) a base case which uses a traditional gas upgrading (chemical adsorption) and a stand-alone liquefaction unit located downstream of the main Bio-SNG plant. Both cases are simulated with Aspen Plus to obtain mass and energy balances. Pinch analysis is conducted for both cases to investigate utility demands as well as the potential to convert excess process heat to shaft work to improve the energy performance of the processes. The cryogenic unit investigated achieves the targeted product specifications and capacity, and the calculated performance is comparable to published data for commercial cryogenic units in terms of specific power demand and methane loss. The simulation results show that the integrated plant configuration with cryogenic technology has a higher power requirement than the base case. Shaft power outputs are estimated for both the integrated and base cases assuming a steam cycle combined heat and power unit which recovers process excess heat. The estimated work outputs are more than sufficient to cover the process power demands for both cases; thus the excess power can be exported to the grid. The base case achieves a slightly higher overall energy efficiency compared to the integrated case, whereas the cold gas efficiency is higher for the integrated case due to low methane loss. Cryogenic technology is still under development, therefore there is a high potential for performance improvement by application of energy efficiency measures. In addition, high purity liquid CO2 is produced at very low temperature as a by-product which could generate additional revenue.
Keywords: Energi; Hållbar utveckling; Kemiska processer; Energy; Sustainable Development; Chemical Process Engineering